Exploring of Students' Ability to Solve Geometry Problems Based on Van Hiele's Level of Thinking - Andira, Ayu; Darwis M, Muhammad; Syam, Haerul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
Based on Van Hiele's level of thinking, this study intends to investigate students' ability to solve geometric problems. Polya's heuristic of problem-solving steps is used to assess problem-solving ability. A qualitative, descriptive study is the form of research used in this case. The Van Hiele Geometry Test (VHGT), problem-solving aptitude assessments, and interviews were used. Based on Van Hiele's level of thinking, researchers chose three students from a group of 27 students in grade VIII high junior school Terpadu Sheikh Muhammad Ja'far as research subjects. Data collection methods include tests and interviews. Data condensation, data presentation, conclusion drafting, and verification are all research data analysis approaches. The validity of the data is verified using a triangulation of techniques and sources. The findings of the study are: subjects at the pre 0 level only have visual, verbal, and drawing skills. Subjects at level 0 (visualization) were not able to solve the four problem-solving heuristics by Polya. Subjects at level 1 (analysis) were able to reach the second stage of the problem-solving heuristic by Polya. Subjects at level 2 (informal deduction reached the third stage of the problem-solving heuristic by Polya.